Psychometric Properties of a Local Wisdom-Based Science Literacy Instrument for Primary School Students: An Item Response Theory Approach - Nurhasanah; Tri Astari; Elvin Cahyanita; Nuriman (Postgraduate, University of Mataram, 2025)
Science literacy is an essential competency for primary school students to face 21st-century challenges. However, few assessment tools combine strong psychometric quality with cultural relevance. This study aimed to examine the psychometric properties of a local wisdom–based science literacy instrument for primary school students within the Item Response Theory (IRT) framework. The instrument comprised 34 multiple-choice items aligned with science literacy indicators and was administered to 300 fourth-grade students from several schools in Jember, Indonesia. Expert judgment ensured content validity, while empirical analyses using QUEST and R Studio evaluated item performance. The results showed good model fit, excellent reliability (0.97), and well-balanced item difficulty levels, confirming the instrument’s ability to measure a wide range of student abilities. Person–item maps and item characteristic curves indicated high discriminative power and measurement precision. Embedding local wisdom elements enhanced cultural authenticity and student engagement in science learning. Overall, the instrument demonstrated strong psychometric and contextual validity, offering a reliable tool for assessing science literacy in primary education. Its application can help teachers identify learning needs and design culturally responsive instruction. Future studies should extend validation to broader cultural contexts and refine items for students with lower ability levels.